Analysis of Banking Innovation with Business Model Canvas in BPRS Suriyah Cilacap Central Java - Nisrina Anggi Syahputri (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The 4.0 industrial revolution has encouraged technological innovations that have disrupted or fundamental changes to people‟s lives. Unexpected changes become a phenomenon that will often appear in the industrial revolution era 4.0. To maintain the existence of an company, not only the right strategy is needed but also knowing the Islamic banking business model in BPRS is an important thing to consider. Besides, the business model in the BPRS must continue to be innovated. This research that entitled “Analysis of Banking Innovation with Business Model Canvas in BPRS Suriyah Cilacap Central Java”, has problem statements about how the banking innovation and the SWOT analysis of each Business Model Canvas‟s element in BPRS Suriyah Cilacap. The purpose of this research are to find out the banking innovation and the SWOT analysis of each Business Model Canvas‟s element in BPRS Suriyah Cilacap. This type of research is field research by descriptive qualitative method. The research was collected by observation, documentation and interviews with informants who have good knowledge about marketing and operational BPRS Suriyah Cilacap. The result of this research mentioned that even though BPRS Suriyah Cilacap has good achievements, it must continue to really makes a business model in his banking innovation, then test and analyze it. It still has shortcomings in executing marketing plans. It must continue to make better customer relationships as opportunity to make a big market and must have good action on the challenges of technological development.